Lean-verktyget värdeflödesanalys i projektprocesser : En fallstudie vid trafikverket Region Nord - Halvarsson, Tomas (2012)
Value Stream Mapping is a tool used in the management concept called Lean, which is a business strategy developed by the Japanese company Toyota. A Value Stream Mapping is performed to identify and visualize tasks that within a process create value or imply waste. The mapping is then used as a starting-point to make improvements from a holistic perspective. Since the mid-1990s lean has become increasingly common among organizations in the Western world and the trend has gone from being a strategy for the shop floor to leading administrative organizations as well. The view of ordinary tasks as well as projects as recurrent processes means that lean can be applied to most types of businesses. The department of Investments at Trafikverket in Luleå is exclusively project-oriented and manages the construction and re-enforcing of roads and railways. Trafikverket, established in 2010, has a need for greater efficiency and a clear interest in lean as a strategy for the future. This study describes the project process from a lean perspective, and can thus make a valuable contribution to the organization's future choices regarding business strategy. The purpose of this study is to identify value adding activities and waste in the feasibility study regarding re-enforcing of roads. Another purpose is to make suggestions about how to improve the flow of activities in the feasibility study.The thesis was conducted as a case study which was initiated by a literature review. Furthermore, a mapping of the feasibility study was conducted through a workshop, additional interviews as well as additional process mapping. The subsequent analysis was performed with the support of the theory from the literature study.The conclusions regarding applying Value Stream Mapping in project processes are that the tool gives a good overview of the value stream and identifies many of the problems that may exist at a higher level. It appeared that a project process which includes several external organizations requires considerable resources if ...